Assessment of blood types of Ragdoll cats for transfusion purposes. (8th May 2013) - Proverbio, Daniela; Spada, Eva; Perego, Roberta; Della Pepa, Alessandra; Bagnagatti De Giorgi, Giada; Baggiani, Luciana
<x xml:space="preserve">Abstract</x> Background Transfusion of compatible blood types ensures the vitality of transfused erythrocytes and avoids transfusion reactions. Cats with types A, B, and AB blood should receive transfusions of the same blood type. In a feline blood donor program, it is therefore essential to have blood donors of all blood types available. Objectives The objectives of this study were the identification of the 3 feline blood types in Ragdoll cats, the comparison of their frequencies with those of Domestic Shorthair (DSH) cats, and the determination of whether Ragdolls are suitable donors in a feline blood donor program. Methods The blood type was determined by gel column agglutination from Ragdoll cats. The relationships between phenotypic traits, the origin of the cats, and the different blood types were examined. The frequencies for potential transfusion reactions and the risk for neonatal isoerythrolysis (NI) were estimated. Results Of 61 typed Ragdolls, 77.1% had type A, 4.9% type B, and 18% type AB blood. The frequency of blood type A in Ragdolls was lower than in DSH cats (P = .02), while the frequency of blood type AB in Ragdolls was higher than in DSH cats (P = .0002). No relationship was found between blood type and origin of the cat or phenotypic traits. The estimated frequencies of major and minor transfusion reactions following an unmatched transfusion between Ragdolls (donors and recipients), Ragdoll donors and DSH recipients, and DSH donors and Ragdoll recipients were 4.7%, 6.7%, 4.6%, and 18.5%, 20.8%, 7.6%, respectively. The frequency of kittens at risk for NI was 5%. Conclusion The presence of all 3 feline blood types and a relatively high incidence of AB type cats make Ragdolls an ideal donor breed to include in feline blood transfusion programs.